The Impact of Common Problems between the Sectors of Industry and Capital and Ways of their Solutions in the Russian Federation - Badwan, Nemer Louay (Journal of Economic, Administrative and Legal Sciences, 2017)
This study summarizes the impact of common problems between capital and industry sectors and aims to find solutions to these problems to reduce them or to reduce them. It also clarifies the resemblance and comparison of technology to the sectors of industry and capital in Russian Russia. Russia's total over the previous years, and show what happened in the Russian financial market following the withdrawal of many capital and investors from within Russia to abroad, and also shows us this study also the rotational nature of capital in Russia, as this study shows some of its objectives as a most important explanation The capital and industry sectors, their success factors and competitiveness in their application. It also shows the impact of capital financing on industries, clarifying the role of capital finance in various investment projects and in different sectors of industry, and summarizes the scientific and practical concept of capital and industry sectors. And the process, and this can be seen through analytical, graphical and statistical tables within the Russian market in terms of products, profits and losses of the Russian industries by percentages, and the exposure of some Russian investments within Russia, As well as some of the dynamics of consumption within Russia in terms of expenditures, exports, imports and expenditures, and the structure of small and medium-sized enterprises in percentages in terms of production and consumption In the various sectors of Russian industry. The study also summarizes the role of the Russian financial market in the national economic activity and the ratios of fixed assets and the total amounts invested and taxes imposed on them. The study also examined the financial and industrial activities of most of the industrial sectors in Russia and their impact on the economic situation inside the country.
Keywords: Russian Federation; Capital; Industry; Small and Medium and large Enterprises; Finance; Innovation; Strategic